Contested Modernism: Rubén Darío against medical discourse, faith, and the yellow press (Anclajes, 2026)
This article analyzes the status of Spanish American modernist literature and the figure of the artist in the late 19th century, in two texts by Rubén Darío initially published in the press: the short story “El pájaro azul” (“The Blue Bird”), later included in Azul... (Santiago de Chile, 1888), and the chronicle “Azul,” published in the Buenos Aires newspaper Tribuna in 1893 under the pseudonym Des Esseintes. The article examines the intertextual connections between these pieces and medical and religious discourse, as well as journalistic sensationalism, in order to show how Darío argues for the insertion of the writer into the literary market while sustaining a critique of these dominant discourses. Within this framework, literature is legitimized as an autonomous discourse, while recognizing its fragility in the face of the conditions of modernity and the cultural market.
Keywords: Rubén Darío; Spanish American literature; Literary criticism; 19th century; Spanish America